The current and future state of companion diagnostics - Agarwal A; Ressler D; Snyder G (Dove Medical Press, 2015)
Amit Agarwal,1 Dan Ressler,2 Glenn Snyder1 1Deloitte Consulting LLP, San Francisco, CA, USA; 2Deloitte Consulting LLP, Philadelphia, PA, USA Abstract: Companion diagnostics are an indispensable part of personalized medicine and will likely continue to rapidly increase in number and application to disease areas. The first companion diagnostics were launched in the 1980s and in the face of significant initial skepticism from drug developers as to whether segmenting a drug's market through a diagnostic was advisable. The commercial success of drugs such as Herceptin® (trastuzumab) and Gleevec® (imatinib), which both require testing with companion diagnostics before they can be prescribed, has moved the entire companion diagnostic field forward. From an initial start of a handful of oncology drugs with corresponding diagnostics, the field has expanded to include multiple therapeutic areas, and the number of combinations has grown by 12-fold. Based on drugs in clinical trials, the rapid growth will likely continue for the foreseeable future. This expansion of companion diagnostics will also have a global component as markets in Europe will evolve in a similar but not identical pattern as the US. One of the greatest challenges to future growth in companion diagnostics is aligning the incentives of all stakeholders. A major driver of growth will continue to be the economic incentives for drug developers to pair their products with diagnostics. However, diagnostic companies are caught between the conflicting demands of two major stakeholders, pharmaceutical companies on one hand and payers/providers on the other. Regulators are also becoming more demanding in aligning development time lines between drugs and diagnostics. In order to survive and prosper, diagnostic companies will need to think more broadly about companion diagnostics than the historical match between a specific drug and a single diagnostic. They will also have to continue the process of consolidation and global expansion that the industry has already begun. Despite these potential obstacles, companion diagnostics have become one of the hottest areas of deal making in the diagnostic space in recent years, and the future trends continue to look bright. Keywords: companion diagnostics, theranostics, personalized medicine, prognosis, monitoring